Simultaneous Effect Of Temperature And Time Of Deacetylation On Physicochemical Properties Of Glucomannan - Dyah Hesti Wardhani; Fatoni Nugroho; Nita Aryanti; Aji Prasetyaningrum (ASEAN Journal of Chemical Engineering, 2018)
The presence of acetyl group in the backbone of water-soluble glucomannan is responsible for its solubility. This solubility requires being modified to support glucomannan application as an encapsulant. Removing the group by deacetylation reduces the solubility. This work was aims to study simultaneous effect of temperature and time of deacetylation on glucomannan physicochemical properties. The deacetylation was conducted in ethanol using Na2CO3 at various times (2, 4, 8, 16, 24 and 28 h) and temperatures (room temperature, 40, 50, and 60°C). The deacetylated samples were subject to degree of deacetylation (DD) as well as solubility and swelling analysis in pH 1.2 and 6.8. DD was in positive correlation with deacetylation time and temperature. The solubility of the deacetylated glucomannan at both pHs decreased along with the deacetylation time. A reverse trend was found for swelling determination at both pHs. Increasing deacetylation temperature showed a positive impact in swelling determination but not occuring on the solubility. Interestingly, the swelling and solubility were lower at pH 1.2 than those at pH 6.8. These results showed physicochemical of deacetylated glucomannan was pH sensitive, hence have a potency as an excipient of controlled-release drug delivery system.